Inovasi Layanan Kependudukan Duta Hatiku (Dukcapil Tanggap Bencana Harapan Timbul Kembali Utuh dari Disdukcapil Sidoarjo - Mimik Indayana; Widyawati Widyawati; Nihayatus Sholichah (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This research aims to analyze the innovation in population services, called Duta Hatiku (Dukcapil Tanggap Bencana Harapan Timbul Kembali Utuh/Civil Registration Disaster Response: Hope Rises Again Completely), implemented by the Department of Population and Civil Registration (Disdukcapil) of Sidoarjo Regency. This innovation was developed as a quick response service for disaster victims who lost their identity documents. Drawing on the public service innovation theory of Mulgan and Albury, this study examines the novelty, implementation, and impact of the Duta Hatiku program. This qualitative research employs a descriptive approach, with data collected through in-depth interviews, observation, and documentation at Disdukcapil Sidoarjo during May-July 2025. Informants include program managers, field officers, disaster victims as service beneficiaries, and related stakeholders. The results indicate that the Duta Hatiku innovation has successfully provided rapid population document recovery services to disaster victims, with an average service completion time of only 2-3 days, compared to the standard 14 days. The program utilizes mobile service units equipped with portable equipment for on-site document processing at disaster locations. Since its implementation, the program has served 2,847 disaster victims from various incidents, including floods, fires, and landslides. The innovation demonstrates strong characteristics of novelty in service delivery approach, significant improvement in service accessibility, and positive impact on community resilience. This study recommends strengthening coordination with disaster management agencies, expanding mobile unit capacity, developing integrated database systems, and replicating the model to other regions.